Building System for Measuring The Achievement of Expected Learning Outcomes at Program Level – Application Model at Ho Chi Minh City University of Technology and Education - Phan, Thị Thu Thủy; Pham, Huy Tuân; Vo, Xuân Tiến (Journal of Technical Education Science, 2023)
The quality of training programs is an increasingly concerned by society. The achievement of the program learning outcomes (PLO) is one of the conditions for students to be considered and recognized for graduation according to the Training regulations at the university level promulgated together with Circular No. 08/2021/TT-BGDĐT and also is a mandatory requirement of the AUN-QA program quality assessment criteria version 4.0 of the ASEAN University Network - Quality Assurance. Currently, universities in Vietnam are in the early stages of developing and forming related measurement methods, tools, processes and procedures. The authors have used quantitative combined with qualitative research through feedback from lecturers and the results of measuring the achievement of program learning outcomes, which has been piloted at the Ho Chi Minh City University of Technology and Education in 3 academic years 2019-2020, 2020-2021 and 2021-2022, the article presents the implementation status from which to propose an overview of PLO measurement model, procedure and guidelines for measuring the quality of each training program by the actual conditions at HCMUTE to get started applying from the academic year 2022-2023 to ensure the training quality of the University, and to meet the requirements of the training regulations and the domestic as well as international quality assessment/accreditation criteria.